2016
DOI: 10.1093/nc/niw014
|View full text |Cite
|
Sign up to set email alerts
|

Implicit memory for words heard during sleep

Abstract: When we fall asleep, our awareness of the surrounding world fades. Yet, the sleeping brain is far from being dormant and recent research unraveled the preservation of complex sensory processing during sleep. In wakefulness, such processes usually lead to the formation of long-term memory traces, being it implicit or explicit. We examined here the consequences upon awakening of the processing of sensory information at a high level of representation during sleep. Participants were instructed to classify auditory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…It is well known that learning new information acquired while awake depends upon consolidation during sleep [1]; however, whether or not complex new information may be learned while asleep is not yet well established. A study using mice [2] provided evidence that sleep learning is possible by the mammalian brain; studies in humans suggest that simple auditory learning may be possible, but complex verbal learning remains to be demonstrated [1,[3][4][5][6][7]. Current sleep theories posit that teaching new vocabulary during slow-wave sleep is impractical, because this sleep stage does not provide the conditions necessary for learning.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that learning new information acquired while awake depends upon consolidation during sleep [1]; however, whether or not complex new information may be learned while asleep is not yet well established. A study using mice [2] provided evidence that sleep learning is possible by the mammalian brain; studies in humans suggest that simple auditory learning may be possible, but complex verbal learning remains to be demonstrated [1,[3][4][5][6][7]. Current sleep theories posit that teaching new vocabulary during slow-wave sleep is impractical, because this sleep stage does not provide the conditions necessary for learning.…”
Section: Introductionmentioning
confidence: 99%
“…In the recall session, participants were presented with words from the exposure list mixed with new words taken from a new list of masculine and feminine words never presented to participants. Participants were instructed to indicate, for each word, if it belonged or not to the list presented in the morning (classical old/new memory paradigm) (Ebbinghaus, 1885;Eichenbaum et al, 2007;Andrillon and Kouider, 2016). During the recall test, the proportions of novel and old words were identical (N = 24, chance level = 50%).…”
Section: Memory Taskmentioning
confidence: 99%
“…However, little is known about how sleep and its associated rhythms eventually modulate the ability to learn. Past studies revealed the surprising ability of the sleeping brain to form new memories 6 , 7 , 23 , 24 and to process sensory information in a complex and flexible fashion 25 28 ; these results advocate for a more detailed investigation of whether and how memories can be formed during sleep. In particular, the question of how sleep stages modulate environmental learning remains unanswered.…”
Section: Introductionmentioning
confidence: 97%